2012
DOI: 10.1152/ajplung.00072.2012
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic hypercapnia prevents bleomycin-induced pulmonary hypertension in neonatal rats by limiting macrophage-derived tumor necrosis factor-α

Abstract: Sewing AC, Kantores C, Ivanovska J, Lee AH, Masood A, Jain A, McNamara PJ, Tanswell AK, Jankov RP. Therapeutic hypercapnia prevents bleomycin-induced pulmonary hypertension in neonatal rats by limiting macrophage-derived tumor necrosis factor-␣. Am J Physiol Lung Cell Mol Physiol 303: L75-L87, 2012. First published May 11, 2012; doi:10.1152/ajplung.00072.2012.-Bleomycin-induced lung injury is characterized in the neonatal rat by inflammation, arrested lung growth, and pulmonary hypertension (PHT), as observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 76 publications
6
22
0
Order By: Relevance
“…In neonatal rats, our laboratory and others have reported that repeated systemic administration of bleomycin leads to a selective decrease in lung growth, along with arrested alveolarization, vascular hypoplasia, and chronic PHT (15,30,44,52), similar to the lung pathology observed in human infants with severe BPD. We have employed this model to demonstrate a critical role for macrophage influx and macrophagederived tumor necrosis factor (TNF)-␣ in the pathogenesis of chronic PHT (26,44). In the present study, we hypothesized that LTs are upregulated in bleomycin-induced lung injury, and that inhibition of LT biosynthesis or signaling would attenuate inflammation and consequent chronic PHT.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…In neonatal rats, our laboratory and others have reported that repeated systemic administration of bleomycin leads to a selective decrease in lung growth, along with arrested alveolarization, vascular hypoplasia, and chronic PHT (15,30,44,52), similar to the lung pathology observed in human infants with severe BPD. We have employed this model to demonstrate a critical role for macrophage influx and macrophagederived tumor necrosis factor (TNF)-␣ in the pathogenesis of chronic PHT (26,44). In the present study, we hypothesized that LTs are upregulated in bleomycin-induced lung injury, and that inhibition of LT biosynthesis or signaling would attenuate inflammation and consequent chronic PHT.…”
mentioning
confidence: 55%
“…RNA was extracted and reverse transcribed, and quantitative PCR was performed as previously described (44). Primer sequences of genes of interest are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…RNA was extracted and reverse transcribed, and qPCR was performed as previously described (30). Rat primers for cytokines and chemokines upregulated by exposure to bleomycin and for neuronal NOS (NOS1), NOS2, and endothelial NOS (NOS3) were previously published (8,50). Primer sequences for arginases were as follows: arginase I, forward (5=-3=) TACCTGCTGGGAAGGAAGAA and reverse (5=-3=) ACTGCCGTGTTCACAAGTACG; arginase II, forward (5=-3=) ACACTGGGAGGAGACCACAG and reverse (5=-3=) GCAAGGTTTGATCCAGGAAA.…”
Section: Animal Interventionsmentioning
confidence: 99%
“…Previous studies from our group have established a model of repeated systemic bleomycin injection in neonatal rats that results in lung injury mimicking characteristics typical of BPD. This model is a useful tool to help understand mechanisms contributing to lung development and remodeling (31) but also to study the effects of therapeutic interventions aimed at preventing lung parenchymal and vascular injury (31,50,56).The chemotherapeutic agent bleomycin sulfate causes a pulmonary inflammatory and fibrotic response in rodents when instilled as a single intratracheal dose (27) or by repeated intraperitoneal injection (3). Bleomycin-induced lung injury is characterized by induction of proinflammatory cytokines (18), influx of macrophages and other inflammatory cells (23), "emphysematous" lung morphology, and severe PHT (49, 60).…”
mentioning
confidence: 99%
See 1 more Smart Citation